2011
DOI: 10.1111/j.1467-8624.2011.01612.x
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Learning and Transfer of Biological Information From Picture Books to Real Animals

Abstract: Preschool children (N = 104) read a book that described and illustrated color camouflage in animals (frogs and lizards). Children were then asked to indicate and explain which of 2 novel animals would be more likely to fall prey to a predatory bird. In Experiment 1, 3- and 4-year-olds were tested with pictures depicting animals in camouflage and noncamouflage settings; in Experiment 2, 4-year-olds were tested with real animals. The results show that by 4 years of age, children can learn new biological facts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 65 publications
9
94
0
11
Order By: Relevance
“…They conducted a series of experiments which revealed that younger children, especially 3-to 4-year olds, were more likely to transfer solutions from stories about real people than stories about fantasy characters. Several other studies reached similar findings and conclusions (Ganea, Canfield, SimonsGhafari, & Chou, 2014;Ganea, Ma, & DeLoache, 2011;Ganea, Pickard, & DeLoache, 2008;Richert et al, 2009;Richert & Smith, 2011). These studies revealed that realistic storybooks contribute to children's book listening comprehension.…”
supporting
confidence: 74%
“…They conducted a series of experiments which revealed that younger children, especially 3-to 4-year olds, were more likely to transfer solutions from stories about real people than stories about fantasy characters. Several other studies reached similar findings and conclusions (Ganea, Canfield, SimonsGhafari, & Chou, 2014;Ganea, Ma, & DeLoache, 2011;Ganea, Pickard, & DeLoache, 2008;Richert et al, 2009;Richert & Smith, 2011). These studies revealed that realistic storybooks contribute to children's book listening comprehension.…”
supporting
confidence: 74%
“…39-42). Recent evidence reveals that even preschool-aged children learn biological information from children's books and extend it to their reasoning about real situations involving living animals (42,43). Young children are also able to learn science vocabulary when they engage in joint book reading (44).…”
Section: Children's Booksmentioning
confidence: 99%
“…Children can learn facts about objects (Ganea, Pickard, & DeLoache, 2008), animals (Ganea, Ma, & DeLoache, 2011), natural selection (Kelemen, Emmons, Schillaci, & Ganea, 2014), and other types of general knowledge (Marsh, Meade, & Roediger, 2003) from realistic storybooks. In my own work, we showed that children could learn some novel information from a pretend context, but the inferences they drew differed from inferences drawn by children who learned the same information in a real context (Hopkins, Dore, & Lillard, 2014).…”
Section: Curricular Approaches the Tools Of The Mind Programmentioning
confidence: 99%
“…Young children have been shown to learn novel facts from stories. Preschoolers learned novel biological facts about animals (Ganea et al, 2011) and the principles of natural selection (Kelemen et al, 2014) from storybooks; they can even integrate facts learned across multiple stories (Bauer & San Souci, 2010). However, a number of studies have shown that children are more likely to learn novel information from realistic books than from unrealistic or fantastical ones.…”
Section: Emotional Valencementioning
confidence: 99%
See 1 more Smart Citation